(untitled) (Journal of The Colloquium for Information Systems Security Education, 2018)
With the projected global shortfall of almost 2 million Cybersecurity professionals, it become increasingly critical to promote the development of new Cybersecurity degree programs across the U.S. This raises the question of exactly what should these degree programs prepare students to do? In order to examine this question, this study seeks to identify industry priorities for Cybersecurity competencies based on the Department of Labor’s Cybersecurity Industry Model, which creates a tiered set of competencies focusing on the NIST NICE Cybersecurity Workforce Framework categories. The study also seeks to determine if these priorities vary by organizational size or industry.